Aplikasi “Bale Tukang” Berbasis Web di PUPINKA - Made Widiarta; Rodianto; Nusaibah Wafia Santoso (Jurnal Informatika Teknologi dan Sains, 2022)
Bale Tukang Pupinka is a handyman provider based in Sumbawa, West Nusa Tenggara. The community's need for someone who has special abilities in development problems is still difficult to find because of the limited area or distance. This study aims to build a Web-based handyman service information system so that with this system, Bale Tukang in collaboration with Pupinka can appoint an admin to be an operator in using the system so that the process of ordering handyman services goes well and makes it easier for Bale Tukang to control, monitor , and register customers in Sumbawa, NTB. The software development method used in building the system uses the waterfall, while the data collection techniques use interviews, documentation, and literature studies. This system was developed using the PHP programming language, Java Script, CodeIgniter Framework, and MySQL database with software testing using black-box testing. The final result of this research is that the author has succeeded in designing and building a web-based service ordering application so that it can be used by the community as costumers as customers and workers as service providers.